Protection of human rights in liberation theology - Mareteo Tarigan (Journal of Law Science, 2023)
In history, especially in philosophy, there is a lot that tells about liberation in various forms, such as eastern and western philosophy where thoughts about liberation with religious movements and are also in harmony with the historical trajectory that developed until the creation of regulations which we call law. Liberation theology also explains the form of liberation by using theological thinking and adding ontological thinking that draws action from reality.